An Interdisciplinary Framework of Character Building in a Digital-Based Boarding School: Scaffolding Honesly and Discipline - Ramadhan, Affan; Achadi, Muh. Wasith (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This research aimed to investigate the reinforcement of student character education amidst massive digital disruption, hypothesizing that an interdisciplinary model combining technological regulation, institutional rituals, and peer-led interventions significantly enhances moral resilience. Design/methods– The study employed a qualitative descriptive design conducted at a centralized boarding school in Indonesia, chosen for its integrated digital governance. Data collection procedures involved participant observation and in-depth interviews with students and educators, focusing on variables such as digital transparency, peer conformity, and behavioral habituation. Findings – Results indicated that implementing school-based applications for attendance and permits served as effective moral scaffolding, fostering honesty and accountability through transparent data tracking. Furthermore, periodic restrictions on gadget access were found to mitigate dopaminergic-driven distractions, allowing students to practice tangible time discipline and self-regulation. The findings also revealed that peer modeling and cooperative learning successfully transformed